Morphological description of pelvic limb muscles of a specimen of barn owl (Tyto alba) - Morales M., Pamela (2021)
The aim of this study was to describe the musculature of the pelvic limbs of a barn owl (Tyto alba). The specimen has powerful muscles, with a predominance in the development of the flexor muscles over the extensors. In general, there is similarity with the musculature described in other birds, especially raptors; however, it is important to highlight some differences, such as m. iliofibular is well developed and is located caudal and superficial to the m. lateral iliotibial; the m. femorotibial has only two heads; the ms. ambiens and fibular long were not observed in the specimen studied, but m. lateral thigh flexor was observed. The m. long digital flexor has only one head; the ms. perforating and perforated are highly fused and m. extensor digitorum longus I has a small muscular head.